Graphic Applications of Unmanned Aerial Vehicles (UAVs) in the Study of Industrial Heritage Assets. - Martín-Béjar, Sergio; Claver Gil, Juan; Sebastián Pérez, Miguel Ángel; Sevilla-Hurtado, Lorenzo (MDPI, 2020)
As a typology of cultural heritage, a wide range of singularities must to be taken into account when analysing industrial heritage assets. Graphical resources have been usually employed in heritage assets research. Nowadays, Unmanned Aerial Vehicles (UAVs) offer the possibility to obtain images of complex and difficult access areas that cannot be observed on the ground. Furthermore, aerial images allow to analyse heritage assets as a whole. Therefore, in this work, different photographs and videos has been carried out in the San Joaquin sugar cane factory and in the Aguila aqueduct, located in Nerja (Spain). These images have been used to analyse both assets as a set. Different indirect measurements on the factory chimney and irrigation water pond were taken. A Strengths, Weaknesses, Opportunities, and Threats (SWOT) about the use of UAV graphic applications in heritage assets was developed. Finally, the possibilities of conventional photograph technologies and UAV application were compared. Using UAVs allows more image acquisition possibilities than conventional systems. However, both technologies can be complemented and applied together when analysing heritage assets.
Keywords: Patrimonio industrial; Aviones sin piloto; Caña de azúcar - Industria; Fotografía aérea; Industrial heritage; Unmanned aerial vehicles; UAV; Graphic applications; Sugar cane factory; Aerial photograph; SWOT